PERCEPTION OF BANYUWANGI AND BLITAR SOCIETY ON RELIGIOUS HARMONY: PERSEPSI MASYARAKAT BANYUWANGI DAN BLITAR TENTANG KEHARMONISAN BERAGAMA - Latifah, Latifah; Dhamayanti, Wina; Murdana, Kadek Yudi; Kamanitra, Rakyan Paranimmita; Kumoro, Nindyo Budi (Jurnal Pencerahan, 2019)
This study examines the perception of religious harmony in the Banyuwangi and Blitar communities, East Java. The aim is to find out about the level of acceptance of Banyuwangi and Blitar people on the reality of diversity of beliefs and religions in Indonesia. In addition, this paper also looks at how the attitudes of the two communities face various impacts on diversity to create inter-religious harmony. With a quantitative descriptive approach through analysis of minimum and maximum frequency (number) and comparison of relative frequencies (percentages) of two data groups, namely Blitar and Banyuwangi communities, this study shows that people in these two cities: (1) are increasingly critical in seeing problems in relations between-religion; (2) see that maintaining relationships, togetherness, and mutual assistance is an obligation in social life; In addition, (3) insights about other religions are very important to develop religious harmony by not only avoiding prejudice, but also building empathy for people of other religions or beliefs. Putting this into consideration, this research suggests that the existing interfaith forum needs to be more community based